Biomarkers of asthma relapse and lung function decline in adults with spontaneous asthma remission: A population‐based cohort study. Issue 4 (16th November 2022) - Tan, Daniel J.; Lodge, Caroline J.; Walters, Eugene Haydn; Lowe, Adrian J.; Bui, Dinh S.; Bowatte, Gayan; Kandane‐Rathnayake, Rangi; Aldakheel, Fahad M.; Erbas, Bircan; Hamilton, Garun S.; Thomas, Paul S.; Hew, Mark; et al.
Abstract: Background: The extent to which biomarkers of asthma activity persist in spontaneous asthma remission and whether such markers are associated with future respiratory outcomes remained unclear. We investigated the association between sub‐clinical inflammation in adults with spontaneous asthma remission and future asthma relapse and lung function decline. Methods: The Tasmanian Longitudinal Health Study is a population‐based cohort ( n  = 8583). Biomarkers of systemic inflammation were measured on participants at age 45, and latent profile analysis was used to identify cytokine profiles. Bronchial hyperresponsiveness (BHR) and nitric oxide products in exhaled breath condensate (EBC NOx) were measured at age 50. Participants with spontaneous asthma remission at ages 45 ( n  = 466) and 50 ( n  = 318) were re‐evaluated at age 53, and associations between baseline inflammatory biomarkers and subsequent asthma relapse and lung function decline were assessed. Results: We identified three cytokine profiles in adults with spontaneous asthma remission: average (34%), Th2‐high (42%) and Th2‐low (24%). Compared to the average profile, a Th2‐high profile was associated with accelerated decline in post‐BD FEV1 /FVC (MD −0.18% predicted per‐year; 95% CI −0.33, −0.02), while a Th2‐low profile was associated with accelerated decline in both post‐BD FEV1 (−0.41%; −0.75, −0.06) and post‐BD FVC (−0.31%; −0.62, 0.01). BHR and high TNF‐α during spontaneous remission were associated with an increased risk of asthma relapse. In contrast, we found no evidence of association between EBC NOx and either asthma relapse or lung function decline. Conclusion: BHR and serum inflammatory cytokines have prognostic value in adults with spontaneous asthma remission. At‐risk individuals with BHR, Th2‐high or Th2‐low cytokine profiles may benefit from closer monitoring and on‐going follow‐up. Abstract : This study examines the relationship between sub‐clinical inflammation in adults with spontaneous asthma remission and future respiratory outcomes in the Tasmanian Longitudinal Health Study. BHR in adults with spontaneous asthma remission is associated with an increased risk of asthma relapse. Th2‐low and Th2‐high cytokine profiles in adults with spontaneous asthma remission are associated with different patterns of accelerated lung function decline.Abbreviations: BHR, bronchial hyperresponsiveness; FEV1, forced expiratory volume in one second; FVC, forced vital capacity; IL, interleukin; TAHS, Tasmanian Longitudinal Health Study; Th2, T helper 2